2013
DOI: 10.1128/cvi.00120-13
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Detection of Serum Antibody by Dual-Path Platform VetTB Assay in White-Tailed Deer Infected with Mycobacterium bovis

Abstract: Bovine tuberculosis (TB) in cervids remains a significant problem affecting farmed herds and wild populations. Traditional skin testing has serious limitations in certain species, whereas emerging serological assays showed promising diagnostic performance. The recently developed immunochromatographic dual-path platform (DPP) VetTB assay has two antigen bands, T1 (MPB83 protein) and T2 (CFP10/ESAT-6 fusion protein), for antibody detection. We evaluated the diagnostic accuracy of this test by using serum samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 23 publications
2
23
0
Order By: Relevance
“…The uncertainty over the effectiveness of the SICCT in cervids has led to studies of supplementary blood tests that, when used together with a tuberculin skin test, can increase the sensitivity and/or specificity of BTB infection detection: The Dual Path Platform (DPP) VetTB rapid immunochromatographic antibody test (Chembio Diagnostic Systems, Medford, New York, USA) has a published sensitivity and specificity in US white-tailed deer of 65 per cent and 98 per cent, respectively ( Lyashchenko and others 2013 ), and in Spain the DPP VetTB test used in parallel with the comparative skin test (interpretation as in Jaroso and others 2010 ) was found to increase the sensitivity of detection of confirmed infected individuals from 76 per cent (skin test alone) to 97 per cent (skin test-positive plus DPP VetTB-positive combined) ( Boadella and others 2012 ). A more dramatic example of an ineffective skin test being compensated by serology was described in a herd of farmed elk and fallow deer in Nebraska ( Waters and others 2011 ).…”
Section: Btb Testing In Cervids: Options and Usefulnessmentioning
confidence: 99%
“…The uncertainty over the effectiveness of the SICCT in cervids has led to studies of supplementary blood tests that, when used together with a tuberculin skin test, can increase the sensitivity and/or specificity of BTB infection detection: The Dual Path Platform (DPP) VetTB rapid immunochromatographic antibody test (Chembio Diagnostic Systems, Medford, New York, USA) has a published sensitivity and specificity in US white-tailed deer of 65 per cent and 98 per cent, respectively ( Lyashchenko and others 2013 ), and in Spain the DPP VetTB test used in parallel with the comparative skin test (interpretation as in Jaroso and others 2010 ) was found to increase the sensitivity of detection of confirmed infected individuals from 76 per cent (skin test alone) to 97 per cent (skin test-positive plus DPP VetTB-positive combined) ( Boadella and others 2012 ). A more dramatic example of an ineffective skin test being compensated by serology was described in a herd of farmed elk and fallow deer in Nebraska ( Waters and others 2011 ).…”
Section: Btb Testing In Cervids: Options and Usefulnessmentioning
confidence: 99%
“…Chembio DPP technology was used to detect bovine IgG and IgM responses to the polyepitope fusion protein MPB83-MPB70 (14,19). As a detection system, goat anti-bovine IgG and anti-bovine IgM antibodies (Kirkegaard & Perry Laboratories) were conjugated to colloidal gold nanoparticles using Chembio standard procedures.…”
Section: Mpb83/mpb70 Elisa (Idexx M Bovis Ab Test)mentioning
confidence: 99%
“…As a detection system, goat anti-bovine IgG and anti-bovine IgM antibodies (Kirkegaard & Perry Laboratories) were conjugated to colloidal gold nanoparticles using Chembio standard procedures. Serum samples were tested at a dilution of 1:40 in assay running buffer, and results were recorded at 20 min using an optical reader to measure test band reflectance in relative light units (RLU), as described previously (14).…”
Section: Mpb83/mpb70 Elisa (Idexx M Bovis Ab Test)mentioning
confidence: 99%
“…Palmer et al [ 24 ] demonstrated the sensitivity and specificity of the CCT alone to be 97% and 81% respectively in 169 known infected and non-infected WTD. The estimated sensitivity and specificity of DPP in WTD was 65% and 98%, respectively [ 25 ].…”
Section: Introductionmentioning
confidence: 99%